Fog in GATS commitments: Boon or bane? - Rudolf Adlung; Peter Morrison; Martin Roy; Weiwei Zhang (World Trade Organization (WTO), 2011)
The creation of the General Agreement on Trade in Services (GATS), in the Uruguay Round, and its entry into force in 1995 marked a new stage in the history of the multilateral system. It was motivated essentially by the rapid expansion of international services trade within an increasingly open environment in many countries. Given the peculiarities of services trade, including the intangible nature of the products concerned and the need for direct contact between supplier and user in many cases, the Agreement contains a variety of conceptual innovations, including its extension to modes of supply beyond conventional cross-border trade (consumption abroad, commercial presence, and presence of natural persons) and its coverage, and legitimization, of various types of non-tariff restrictions. In turn, the new concepts needed time to be absorbed by the ministries and agencies involved in services trade. Further, the positive-list, or bottom-up, approach to scheduling trade commitments under the GATS meant that great flexibility was given to Members in selecting the sectors concerned and specifying the levels of access provided under individual modes. Thus, not surprisingly, the schedules that emerged from the Uruguay Round, which still account for the majority of current commitments, contain a variety of unclear or superfluous entries that may cause interpretation problems. Their solution could contribute significantly to the clarity and comparability of access obligations across sectors and WTO Members. The scheduling conventions agreed for the Doha Round thus provide specifically for the possibility of technical refinements that leave the substance of commitments unchanged. However, not only was this possibility used more sparingly to date than might have been expected, but additional flaws would be introduced if some current offers were to enter into effect. The following discussion, with a focus on a particular group of entries (market access via commercial presence), tries to explain the scope for such refinements and develop a clearer picture of the areas where further action might be needed.
Keywords: F13; F53; F59; 330; GATS; trade in services; schedules of commitments; GATS